Surgery for non-Hodgkin's lymphoma - Elroy Patrick Weledji; George Enow Orock (Frontiers Media S.A., 2015)
Non-Hodgkin lymphomas (NHLs) are a diverse group of blood cancers derived from lymphocytes that vary significantly in their severity. Surgery is not often used as a treatment because of the efficacy of chemotherapy, biological therapy, radiotherapy and hematopoietic stem cell transplantation. We reviewed the natural history and possible role of surgery for NHL. Surgery may be useful in confirming or refuting an equivocal radiological diagnosis through biopsy, removing symptomatic limited disease from an affected organ and in splenectomy for primary splenic lymphoma. Emergency abdominal surgery for acute complications of NHL provides palliation and diagnosis. There is as yet no consensus as to the optimum treatment for symptomatic limited disease affecting an organ and timing of chemotherapy perioperatively. Prospective randomized trials are required.